2019
DOI: 10.1007/s10096-019-03507-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of the early absolute CD64-expressing neutrophil count and sepsis outcome

Abstract: To evaluate the early absolute CD64/CD15/CD45 neutrophil count as a marker of prognosis of sepsis outcome the absolute CD64/CD15/CD45 count was measured by flow cytometry in 65 patients with confirmed or suspected Gram-negative sepsis and organ dysfunction. Serum interleukin(IL)-8 and interferon-gamma (IFNγ) were measured by an enzyme immunoassay. An absolute count lower than 2500 cells/mm 3 could early discriminate non-survivors with sensitivity 82.9% (OR 3.46, 95%CIs 1.10-10.95, p 0.042). After forward step-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Previous studies found low expression of CD64 molecule on resting neutrophils; however, it increases once neutrophils become activated [ 30 , 31 ]. Based on it, we determined the activation status of neutrophils by detecting the surface CD64 expression firstly.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found low expression of CD64 molecule on resting neutrophils; however, it increases once neutrophils become activated [ 30 , 31 ]. Based on it, we determined the activation status of neutrophils by detecting the surface CD64 expression firstly.…”
Section: Resultsmentioning
confidence: 99%
“…Not only are neutrophils the first line of defense, armed with the ability to recognize and respond to infection in the absence of normal receptor expression, but they are also activated in sepsis to produce reactive oxygen species, nitric oxide, cytokines, proteases, and kinins. Xini et al [ 53 ] discovered that an early absolute CD64/CD15/CD45 neutrophils count lower than 2500/mm 3 is independently associated with unfavorable outcome of sepsis. Another study found that reduced neutrophil CD16 expression predicted an increased risk of death in critically ill patients with sepsis [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative expression of neutrophil CD64 serves as a sensitive and specific laboratory indicator of the presence of sepsis or systemic acute inflammatory response, thus suggestive of a variety of inflammatory conditions ( Xini et al, 2019 ; Hashem et al, 2020 ; Patnaik et al, 2020 ). Levels of CD64 were found to predict the occurrence of advanced appendicitis or PA; CRP levels and CD64 expression on leukocytes could better predict the diagnosis of CA ( Ozguner et al, 2014 ).…”
Section: Single Indexmentioning
confidence: 99%